2020
DOI: 10.1108/ijoes-03-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Authentic leader and internal whistleblowers: testing a dual mediation mechanism

Abstract: Purpose This study aims to extend the understanding of the role of authentic leadership in encouraging subordinates to become internal whistleblowers. The current study aims to seek whether authentic leadership can encourage internal whistleblowing (IW) through employee controlled motivation for IW and moral courage. Design/methodology/approach The samples of this study were 221 employees working at 26 government organizations in one of the provinces located on Sumatera Island, Indonesia. Based on the cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…In this way, employees with high moral courage can determine their value priorities. Prior research has demonstrated how moral courage positively influences employees' ethical behavior, including expressing their ethical concerns, such as reporting fraudulent acts (Anita et al, 2020;Fernando et al, 2021;Sekerka & Bagozzi, 2007). Based on the above discussion, the study puts forth the following hypotheses: Hypothesis 3: Moral courage mediates the relationship between authentic leadership and whistleblowing intention.…”
Section: The Mediating Role Of Moral Couragementioning
confidence: 90%
See 3 more Smart Citations
“…In this way, employees with high moral courage can determine their value priorities. Prior research has demonstrated how moral courage positively influences employees' ethical behavior, including expressing their ethical concerns, such as reporting fraudulent acts (Anita et al, 2020;Fernando et al, 2021;Sekerka & Bagozzi, 2007). Based on the above discussion, the study puts forth the following hypotheses: Hypothesis 3: Moral courage mediates the relationship between authentic leadership and whistleblowing intention.…”
Section: The Mediating Role Of Moral Couragementioning
confidence: 90%
“…The first section of the questionnaire required the respondents to evaluate the authentic leadership of their supervisors by using sixteen measurement items developed by Avolio et al (2007). The questionnaire was used in several previous studies such as research by Anita et al (2020) and Kutluata et al (2017). The items measured four components of authentic leadership, which were selfawareness, internalized moral processing, balanced information processing, and relational transparency.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethical leadership: Leadership style has been recognized as having an important role in determining certain work attitudes and behaviors (Eva et al, 2019;Inceoglu et al, 2018). Previous research has revealed that positive leader behavior can shape productive attitudes and behaviors such as OCB (Cooper et al, 2018;Newman et al, 2017), internal whistleblowing (Anita et al, 2021), knowledge-sharing (Abdillah, 2021) and organizational performance (MallĂ©n et al, 2015). EL is described as "the display of normatively appropriate behavior through individual actions and interpersonal relationships, and the promotion of that behavior to followers through two-way communication, reinforcement, and decision making" (Den Hartog & Belschak, 2012;Brown & Treviño, 2014;Zaim et al, 2021).…”
Section: Theoretical Reviewmentioning
confidence: 99%